The effects and mechanisms of acupuncture for post-stroke cognitive impairment: progress and prospects - Li, Ningcen; Wang, Hui; Liu, Hang; Zhu, Lina; Lyu, Zhongxi; Qiu, Jiwen; Zhao, Tianyi; Ren, Haiyan; Huang, Lihong; Chen, Shuangli; Hu, Xiuwu; Zhou, Liang (Frontiers in Neuroscience, 2023)
Stroke is one of the important causes of both disability and death worldwide, which is very common in older adults. Post-stroke cognitive impairment (PSCI) is a common secondary damage of stroke, which is the main cause of long-term disability and decreased quality of life in stroke patients, which brings a heavy burden to society and families. Acupuncture, as one of the oldest and widely used worldwide techniques in Chinese medicine, is recommended by the World Health Organization as an alternative and complementary strategy for improving stroke care. This review comprehensively summarizes literature from the last twenty-five years, showing that acupuncture can exert strong beneficial effect on PSCI. The mechanisms of acupuncture on PSCI involves anti-neuronal apoptosis, promoting synaptic plasticity, alleviating central and peripheral inflammatory reactions, and regulating brain energy metabolism disorders (including improving cerebral blood flow, glucose utilization and mitochondrial structure and function, etc.), etc. The effects and mechanisms of acupuncture on PSCI reviewed in this study provides scientific and reliable evidence for acupuncture application for PSCI.